FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA SUB SEKTOR PROPERTY DAN REAL ESTATE DI IDX TAHUN 2019 - 2023 - BELLA LISA ANGELINE; HENDRA HENDRA (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
This study aims to analyze the effect of profitability (ROA), investment decisions (PER), capital structure (DER), debt policy (DAR), and company size (LN) on company value (TOBINS_Q) in the property and real estate sub-sector listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. The study uses a quantitative method with secondary data sourced from the annual financial reports of companies listed on the IDX. The research sample was selected using a purposive sampling method, resulting in 37 companies that met the research criteria. Data analysis was carried out using panel regression model. The results of the study show that profitability has a positive and significant effect on company value, while company size has a negative and significant effect. This finding show that more profitable company will increase the company value because many investor will interested to invest their fund. Meanwhile, investment decisions, capital structure, and debt policy do not show a significant effect on company value.